Primary Breast Osteosarcoma: A Case Report and Literature Review - Tsung-Han Tsai; Hsuan-Ying Huang; Yu-Li Su (Journal of Cancer Research and Practice)
Primary breast osteosarcomas are rare. We report an unusual case of a 58-year-old female presenting with a right breast lump for 1 month. Mammography showed an ill-defined, heterogeneous, and coarse calcification measuring 4 cm over the upper inner quadrant of the right breast. She received an upfront partial mastectomy after core needle biopsy showed osteoid-like tissue with the presence of atypical cells and some multinucleated giant cells. The final pathology revealed Grade 3 extraosseous osteosarcoma, osteoblastic type. Four cycles of adjuvant doxorubicin and cisplatin followed by radiotherapy were given due to the close surgical margin. She has since been free of recurrence for 3 years.